Aged fingerprints for DNA profile: First report of successful typing. (September 2019) - Romano, Carlo Giovanni; Mangiaracina, Rosaria; Donato, Luigi; D'Angelo, Rosalia; Scimone, Concetta; Sidoti, Antonina
Highlights: Fingerprint and STR profile for personal identification. Not degraded DNA purified from aged fingerprint. Informative profile from aged fingerprint. Abstract: Fingerprint detection and Short Tandem Repeat (STR) typing are two approaches used for identification of individuals. The main goal of forensic laboratories is the development of a standardized protocol to obtain an STR profile from latent fingerprints, by typing the DNA transferred onto touched objects. The results obtained in this field derive from studies conducted under controlled laboratory conditions. Here, for the first time, we report two different profiles obtained by DNA purified by latent fingerprints enhanced with dactyloscopic powders at a crime scene, 14 years previously. DNA extraction phase was optimized to improve removal of powder and automatically conducted. Despite the low concentration of purified DNA, it was not degraded. Even if quality of the profile is influenced by several factors such as the method of acquisition and storage conditions of the fingerprint, results obtained are adequately informative and could be uploaded to the CODIS database.